Approximate DFT-based methods for generating diabatic states and calculating electronic couplings: models of two and more states. Issue 4 (10th January 2018) - Yang, Chou-Hsun; Yam, ChiYung; Wang, Haobin
Abstract : Four types of density functional theory (DFT)-based approaches are assessed in this work for the approximate construction of diabatic states and evaluation of the electronic couplings between these states. Abstract : Four types of density functional theory (DFT)-based approaches are assessed in this work for the approximate construction of diabatic states and the evaluation of electronic couplings between these states. These approaches include the constrained DFT (CDFT) method, the constrained noninteracting electron (CNE) model to post-process Kohn–Sham operators, the approximate block-diagonalization (BD) of the Kohn–Sham operators, and the generalized Mulliken–Hush method. It is shown that the first three approaches provide a good description for long-distance intermolecular electron transfer (ET) reactions. On the other hand, inconsistent results were found when applying these approaches to intramolecular ET in strongly coupled, mixed-valence systems. Model analysis shows that this discrepancy is caused by the inappropriate use of the two-state model rather than the defects of the approaches themselves. The situation is much improved when more states are included in the model electronic Hamiltonian. The CNE and BD approaches can thus serve as efficient and robust alternatives for building ET models based on DFT calculations.